2014
DOI: 10.1109/jstars.2014.2320960
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Precipitation Estimates by at-Launch Codes of GPM/DPR Algorithms Using Synthetic Data from TRMM/PR Observations

Abstract: The Global Precipitation Measurement (GPM) Core Observatory will carry a Dual-frequency Precipitation Radar (DPR) consisting of a Ku-band precipitation radar (KuPR) and a Ka-band precipitation radar (KaPR). In this study, "at-launch" codes of DPR precipitation algorithms, which will be used in GPM ground systems at launch, were evaluated using synthetic data based upon the Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar (PR) data. Results from the codes (Version 4.20131010) of the KuPR-only, KaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 53 publications
0
29
0
1
Order By: Relevance
“…With regards to the DPR, a diagnosed side‐lobe clutter issue was corrected (Kubota et al ., ), and overall performance demonstrated in Kubota et al . (), Toyoshima et al . () and Iguchi et al .…”
Section: Observational Goals For Gpm Precipitation: Microphysical To mentioning
confidence: 99%
“…With regards to the DPR, a diagnosed side‐lobe clutter issue was corrected (Kubota et al ., ), and overall performance demonstrated in Kubota et al . (), Toyoshima et al . () and Iguchi et al .…”
Section: Observational Goals For Gpm Precipitation: Microphysical To mentioning
confidence: 99%
“…Chen et al [70] found that due to incorrect rain type classification, overcorrection of radar signals, poor performance of the Surface Reference Technique (SRT) module, ground clutter and geometric effects, TRMM PR overestimates the frequency of moderate rain rates. GPM DPR was found to underestimate precipitation rates for rates smaller than 10 mm/h and overestimate for rates above 10 mm/h by using at-launch code and synthetic data based on the TRMM PR data [71]. and some other regions compared with ground radars [68,69].…”
Section: Comparison Of Overall Precipitationmentioning
confidence: 99%
“…A 'Core' satellite in the GPM mission is used to measure the rainfall rate from space and the obtained data serves as a reference to consolidate rainfall measurements from an international network of satellites. The measurement instruments include a multi-channel GPM Microwave Imager (GMI) and the first space-borne Ku/Ka-band Dual-frequency Precipitation Radar (DPR) both of which are carried on the 'Core' satellite [25]. The GMI scans a swath of 885 km and has 13 microwave radiometer channels covering a frequency range of 10-183 GHz; the DPR includes Ku-band and Ka-band precipitation radars with 13.6 GHz and 35.5 GHz frequencies, respectively [26].…”
Section: Introductionmentioning
confidence: 99%